Multiphysics Computing of Challenging Antenna Arrays Under a Supercomputer Framework - Zhang, Hao-Xuan; Zhan, Qiwei; Huang, Li; Wang, Da-Wei; Wang, Yin-Da; Wang, Wei-Jie; Zhao, Zhen-Guo; Zhou, Hai-Jing; Kang, Kai; Zhou, Liang; Yin, Wen-Yan (IEEE journal on multiscale and multiphysics computational techniques, 2023)
A parallel multiphysics simulation solver is developed to solve electromagnetic-thermal-mechanical coupling for some challenging large-scale antenna arrays. To achieve high scalability of supercomputer architectures, we reconstruct the preconditioned BiCGSTAB method and the non-overlapping domain decomposition method, so that the most resource-intensive matrix factorization steps can be performed in parallel independently within subdomains. The electromagnetic and thermal fields are solved separately, while coupled through the dissipated power and the temperature-dependent material parameters; after thermal steady state is reached, the mechanical simulation is stimulated subject to the temperature rise. The accuracy of electromagnetic-thermal coupling and thermal stress solution are first validated, and then the strong/weak parallel scalability experiments of the developed multiphysics solver are performed on supercomputer. Finally, an extremely challenging antenna array is simulated using the proposed solver, where to our best knowledge we bring the scale of multiphysics simulations excited by frequency-domain electromagnetic fields to the order of billion unknowns for the first time.